Evaluation the Expression of Endoglin (CD105) & IL-3 Level of Pregnancy Women with Antiphospholipid Syndrome - Salih, Manal (University of Thi-Qar Journal of Science, 2019)
This study designed to describe the histopathology changes of human placenta for pregnancies women with APA and normal pregnancies, also to estimate placental Immunohistochemical staining (IHC) expression patterns of endoglin in pregnancies with APA compared to normal pregnancies and quantify IL-3 serum level for both groups by using ELISA test. The histopathology results showed that arteries with degenerated media were associated with inflammatory cells and areas of hemorrhage were associated with moderate placentitis with inflammatory cells and fibrosis; also congested capillaries and blood vessels. The immunostaining results showed decrease in expression of endoglin in PAS pregnancy compared than healthy pregnancy with significant difference (43.3% versus 75 % ; p ≤ 0.05) . Some arteries with degeneration of sub region with hyalinization and congestion. The evaluation of the serum levels of IL-3 were showed the elevated level in healthy pregnancy (599.15 ±SE68.59 pg/ml) compared to APS pregnancy (264.96± SE 38.28 pg/ml) with significant difference (P ≤ 0.05).